Development of aluminium-based metal-dielectric structures with energy-saving properties - Борисова, Александра Владимировна; Вербицкий, Владимир Григорьевич; Мачулянский, Александр Викторович; Родионов, Михаил Кузьмич (Eastern-European Journal of Enterprise Technologies, 2014)
The spectral-selective characteristics of transparent metal-dielectric structures with energy-saving properties based on nanoscale aluminum layers are investigated. The technique for calculating reflection and transmission coefficients of metal-dielectric structures based on the transfer matrix method which allows to determine the relationship between the electromagnetic response of the metal-dielectric coating with microstructure and optical parameters of its components is presented. The results of numerical simulation of the spectral-selective characteristics of reflection and transmission coefficients of optically transparent metal-dielectric structures with nanoscale aluminum layers with a thickness of 1-100 nm and antireflection coatings based on aluminum oxide or nitride with a thickness of 200 nm are given. It was found that aluminum-based coatings with thicknesses of up to 5 nm have low-emissivity properties, and with thicknesses of more than 20 nm - reflexive properties. Recommendations on practical use of aluminum-based metal-dielectric structures in energy-saving technologies and possibilities of technological formation of such structures in a single process cycle by vacuum reactive ion-plasma sputtering are presented.